ER-Phagy: A New Regulator of ER Homeostasis - Yang, Ming; Luo, Shilu; Wang, Xi; Li, Chenrui; Yang, Jinfei; Zhu, Xuejing; Xiao, Li; Sun, Lin (Frontiers in Cell and Developmental Biology, 2021)
The endoplasmic reticulum (ER) is one of the most important cellular organelles, and its homeostasis is crucial for many life activities. Under external stimulation, ER stress induces the unfolded protein response (UPR) and ER-associated degradation (ERAD) to maintain ER homeostasis. However, persistent ER stress can lead to cell damage. ER-phagy is a selective form of autophagy that ensures the timely removal of damaged ER, thereby protecting cells from damage caused by excessive ER stress. As ER-phagy is a newly identified form of autophagy, many receptor-mediated ER-phagy pathways have been discovered in recent years. In this review, we summarize our understanding of the maintenance of ER homeostasis and describe the receptors identified so fa. Finally, the relationship between ER-phagy and disease is also discussed.